Academics' perspectives of the teaching and development of generic employability skills in science curricula. Issue 2 (23rd February 2020) - Sarkar, Mahbub; Overton, Tina; Thompson, Christopher D.; Rayner, Gerry
ABSTRACT: Graduate employability is a key issue for higher education as new graduates face a highly competitive and rapidly changing employment sector. To maximise their likelihood of employment, graduates need to be able to demonstrate the skills and attributes most valued by employers. Employers, however, have long criticised the ability of graduates to contribute effectively to the workplace, especially due to a perceived lack of generic employability skills. This indicates a possible mismatch between the skills required by employers and those possessed by graduate applicants. This study addresses a gap in the scholarly literature regarding employability skills – the perspectives of science academics at an Australian and UK university regarding the promotion of generic employability skills in the subjects they teach. More specifically, this article discusses academics' perspectives regarding: (a) which of the targeted generic skills were developed and assessed through their science units, and (b) the approaches used to promote the targeted skills and any associated challenges in employing those approaches. The discussion explores how shifting from traditional transmissive pedagogies to more problem-based approaches and embedding reflection into pedagogy and assessment practices would contribute to promoting the skills employers increasingly demand from science graduates.